Transformasi Sistematika Kamus Bahasa Arab: Kajian Metodologis dan Kontribusi Tokoh Leksikografi - Roni, Aji; Ashadi, Munir; Susiawati, Iis (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Dictionaries serve as essential tools in Arabic language learning, functioning not only as sources of word meanings but also as reflections of linguistic systems and scholarly paradigms of their time. This paper examines the systematics of Arabic dictionary compilation, both classical and modern, while analyzing the contributions of key figures such as Khalil ibn Ahmad al-Farahidy, Fairuzabadi, and Az-Zamakhshari to the development of Arabic lexicography. Employing a literature review method with a descriptive-analytical approach, the study explores two dominant organization systems—root-based (mu?jam q?m?s?) and alphabetical (mu?jam hij???)—each with its own advantages and limitations. The paper also highlights the significant shift toward digital dictionaries like ArabDict and Almaany, which integrate phonetic, morphological, and user-access features. This study concludes that understanding both compilation systems, along with the contributions of key lexicographical figures, is essential for optimizing the function of dictionaries as tools for both Arabic language learning and preservation, particularly in addressing the challenges and meeting the needs of users in the digital era.